Seed reproduction of sweet potato (Ipomoea batatas) variety Agrosavia Aurora in Colombia - Espitia Montes, Amaury Aroldo (2021)
Introduction. The species Ipomoea batatas (L.) Lamb is a dicotyledonous plant of the Convolvulaceae family, native to the tropical zone of America. Objective. To determine cutting age and stem segments of sweet potato variety Agrosavia Aurora in order to obtain quality cuttings for sowing. Materials and methods. The study was carried out at the Turipana Research Center of AGROSAVIA, where the production technology of sweet potate cuttings at different cutting ages and stem segments was evaluated. A split block design with 3 replications was used and sprouting percentage, field yield, and economic return were evaluated. Results. Segments cut at 60 and 90 days after sowing (DAP) showed higher sprouting, with values of 84.7 and 74.9%, respectively; statistically exceeding that of segments cut at 120 DDS (67.9%). Sprouting of segments from the apical and preapical portion of the stem were 83.4 and 80.2%, respectively. In root yield, the highest values were obtained with cuttings from segments cut at 60 DDS (26 903 kg.ha-1), which presented statistical differences with respect to those cut at 90 and 120 DAP, as the latter presenting the lowest yield (18 679 kg.ha- 1). Regarding type of seed, the one with the highest production was obtained through the apical segment (25 309 kg.ha-1) without being statistically different from the preapical (24 296 kg.ha-1), and also exceeded in production that of the third (20 504 kg.ha-1) and fourth segment (17 578 kg.ha-1). Conclusion. Apical and preapical segments with a cut-off age of 60 DAP were the best for obtaining cuttings for planting sweet potatoes.